Evaluasi Program Kampung Keluarga Berkualitas di Kampung Canggoang Kelurahan Juhut Kecamatan Karang Tanjung Kabupaten Pandeglang - Fazira Az-Zahra, Zulfa; Handayani, Riny; Rizkiyani, Tiwi (Policy, Law and Political Research Center, 2024)
The Indonesian government has launched the Family Planning Program (KB) as a strategic step to address various population-related challenges. This study aims to evaluate the Kampung Keluarga Berkualitas (Quality Family Village) Program in Kampung Canggoang, Juhut Village, Karang Tanjung District, Pandeglang Regency. The theory used in this research is William N. Dunn's theory. This study employs a descriptive qualitative method. Data collection techniques used include interviews, observation, and documentation. The data analysis technique used is interactive data analysis from Miles and Huberman. The research findings indicate that the evaluation of the Kampung Keluarga Berkualitas Program in Kampung Canggoang, Juhut Village, Karang Tanjung District, Pandeglang Regency, suggests that the program has generally not succeeded in achieving its intended goals. This is due to the uneven training provided to KB village managers, a shortage of workforce, inadequate budget, the irregular updating of data at the Data House Secretariat, the unavailability of reports from each activity group, and low contraceptive use. Therefore, it requires good cooperation between the government, KB village officers, and the community. This cooperation is crucial to improve the program's effectiveness and ensure its proper implementation.